Об устойчивости трехслойных неоднородных стержней в нелинейно упругой среде - Исалы, Биллура Элман кызы; Мамедли, Рамил Элман оглы (НТУ "ХПИ", 2015)
В статье исследуется задача устойчивости трехслойных неоднородных прямолинейных стержней на нелинейно упругом основании под действием сжимающих нагрузок. Здесь предполагается, что стержень находится в неравномерном температурном поле и модули упругости материала слоев зависят от температуры. Для упругого основания принимается нелинейная модель и предполагается, что гипотеза плоских сечений справедлива для всей толщины элемента стержня. В общем виде получено уравнение устойчивости рассматриваемого стержня и для конкретного случая найдена формула для определения критической нагрузки.

We study the problem of three-layered nonhomogeneous rectilinear rods on an nonlinear elastic foundation under the pressure of compressive loads in this article. It is assumed that the rod is in the uneven temperature field and the elasticity modules of the material layers depend on temperature. For the elastic foundation of nonlinear model is accepted and it is assumed that the hypothesis of plane sections is valid for the entire thickness of the element of the rod. In general, we achieve the steadiness equation of the considered rod, and a formula is found for determining the critical load in the certain case. The solution of the problem is obtained by the Bubnov-Galerkin method for a specific case of inhomogeneity of the material layers of the rod made calculations and built specific graphics.Numerical calculations show that the neglect of the inhomogeneity of the material layers can lead to significant errors in the determination of critical materials.
The stability of nonhomogeneous three-layered rods in nonlinear elastic foundation
Keywords: сжимающие нагрузки; температурное поле; уравнение устойчивости; критическая нагрузка; nonhomogeneous three-layered rod; temperature; stability; critical load